Effects of heat and different humidity levels on aerobic and anaerobic exercise performance in athletes - Zhao, J.; Lorenzo, S.; An, N.; Feng, W.; Lai, L.; Cui, S. (Journal of Exercise Science & Fitness, 2013)
Previous studies suggest that the maximum oxygen uptake (VO2max) and the Wingate anaerobic test performances are decreased in hot environments, but it is unknown whether humidity changes in a hot environment further affect the results of the VO2max and Wingate anaerobic test. Nine male athletes performed VO2max and Wingate anaerobic tests under three environmental conditions: (1) 21 °C/20% relative humidity (R.H.) (control); (2) 33 °C/20% R.H. (hot-dry); and (3) 33 °C/80% R.H. (hot-wet). The participants' weight, oral temperature, and skin temperature were recorded pre-exercise and postexercise. The heart rate was monitored continuously throughout the exercise. Compared to the control condition, the hot-dry and the hot-wet conditions had lower VO2max values (control at 3779.0 ± 234.3 mL/min vs. hot-dry at 3528.2 ± 467.4 mL/min and hot-wet at 3595.9 ± 274.6 mL/min; p < 0.05). However, there was no difference in the VO2max between the hot-dry and the hot-wet conditions. A decrease in the postexercise oral-to-skin temperature gradient was strongly correlated with decreased VO2max (mL kg-1 min-1) in all conditions (r = 0.835, p < 0.001). There was no significant difference between the conditions in the peak power and anaerobic capacity during the Wingate anaerobic test. The VO2max was impaired in the hot-dry and in the hot-wet conditions, compared to the control condition; however, the different humidity levels (i.e. hot-dry vs. hot-wet) had no effect on the VO2max. The postexercise oral-to-skin temperature gradient was in line with the variance in VO2max in all three different environmental conditions. The Wingate anaerobic test performance was not affected by the hot-dry or the hot-wet conditions, compared to the control environment. These results suggest that different relative humidity conditions do not affect the VO2max or the Wingate anaerobic test performance in hot environments.